Effect of routine postdilatation on final coronary blood flow in primary percutaneous coronary intervention patients without angiographic stent expansion problems. (11th July 2018) - Soylu, Korhan; Ataş, Ali Ekber; Yenerçağ, Mustafa; Akçay, Murat; Şeker, Onur; Aksan, Gökhan; Gülel, Okan; Şahin, Mahmut
Abstract : Inadequate expansion of coronary stents is associated with stent thrombosis in early stage and with stent restenosis in later stages. Postdilatation (postD) performed using non-compliant balloons improves stent expansion. However, use of this ballooning strategy in primary percutaneous coronary intervention (PPCI) has not been evaluated adequately. Patients who presented with ST segment elevation myocardial infarction (STEMI) and underwent PPCI were included in the present study. Patients were randomized into two groups as those for whom postD was performed (n=62) and those for whom postD was not performed (n=62). Coronary blood flow was evaluated using the thrombolysis in myocardial infarction (TIMI) flow and TIMI frame count (TFC). Total of 124 patients with STEMI were included in the study. There was no difference with respect to baseline TIMI flow, culprit coronary artery and MI localization. However, slow-reflow rate (14.5% vs 35.5%, p=0.007) and final corrected TFC (28.9±16.9 vs 37.0±23.1, p=0.028) were significantly higher in the postD group. Multivariate regression analysis showed postD as an independent variable for slow reflow (OR 11.566, 95% CI 1.633 to 81.908, p=0.014). In our study, routine postD during PPCI was found to be associated with an increased risk of slow reflow in patients without angiographic stent expansion problems.